Insights into rapid composting of paddy straw augmented with efficient microorganism consortium - Anamika Sharma; Richa Sharma; Anju Arora; Raghubir Shah; Arjun Singh; Kumar Pranaw; Lata Nain (International Journal of Recycling of Organic Waste in Agriculture)
Background The objective of this study was to develop a consortium of effective microorganisms to hasten the composting process and to reduce the composting period. Results An efficient microorganism (EM) consortium was developed using Candida tropicalis (Y6), Phanerochaete chrysosporium (VV18), Streptomyces globisporous (C3), Lactobacillus sp. and enriched photosynthetic bacterial inoculum for rapid composting of paddy straw. Paddy straw was amended with poultry droppings to narrow down its C:N ratio for faster degradation. Composting was carried out in open pits with EM consortium and compared with compost inoculant (CI) consisting of Aspergillus nidulans (ITCC 2011), Trichoderma viride (ITCC 2211), Phanerochaete chrysosporium (NCIM 1073) and A. awamori (F-18). Changes in biochemical and physiochemical parameters like C:N ratio, pH, EC and humus were studied over a period of 60 days to test compost maturity and stability along with microbial and extracellular hydrolytic enzyme activities. Paddy straw amended with EM and CI hasten the composting process by bringing C:N ratio down to 15:1 and achieving a total humus content of 4.82 % within 60 days. High activity of hydrolytic enzyme carboxymethyl cellulase (CMCase) (0.43 IU/g) and microbial activity in terms of dehydrogenase (158.64 lg TPF/g/day) was observed in this treatment. The activity of xylanase was positively correlated (r = 0.987) with alkali-soluble carbon. Conclusion This study illustrates the importance of microbial bioaugmentation to hasten the composting process of paddy straw to produce quality compost.